Tax policy as a mechanism to support economic diversification in Algeria - zanat, Samir; boutiara, antar (Journal of Research in Finance and Accounting, 2021)
The research aims to know the Tax policy tools adopted to encourage and diversify production at the level of various economic sectors. It also aims to identify the extent of the contribution of the added value achieved in each sector to improving the diversification index of the Algerian economy. It was concluded that adopting a tax policy on various tools to achieve the goal of economic diversification, through exemptions and tax reductions directed at some activities, or by imposing duties on some local or imported products destined for the national market and exempting local products destined for export from them, contributed to the development The added value in some economic sectors and in the improvement of the economic diversification.